2017
DOI: 10.1186/s12909-017-0866-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting training transfer in health professionals participating in quality improvement educational interventions

Abstract: BackgroundPredictors of quality improvement (QI) training transfer are needed. This study aimed to identify these predictors among health professionals who participated in a QI training program held at a large hospital in the United States between 2005 and 2014. It also aimed to determine how these predictive factors facilitated or impeded QI training transfer.MethodsFollowing the Success Case Method, we used a screening survey to identify trainees with high and low levels of training transfer. We then conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
(21 reference statements)
2
18
0
Order By: Relevance
“…Our findings are similar to results of Eid and Quinn37 in a study of residents’ training in improvement techniques. They found that the outcome of training on improvement capabilities was multifactorial: (1) trainee characteristics (2) training course and (3) work environment.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are similar to results of Eid and Quinn37 in a study of residents’ training in improvement techniques. They found that the outcome of training on improvement capabilities was multifactorial: (1) trainee characteristics (2) training course and (3) work environment.…”
Section: Discussionsupporting
confidence: 90%
“…This close link between the content of the training and daily practice was highly appreciated by the participants in this study, as well as in other studies [22,32]. This, in turn, could potentially have a positive impact on IPs' adherence to the guideline in practice, since participants indicated their intention to continue using the guideline [41]. This is important additional information with respect to broad implementation in the future, as it was derived directly from the stakeholders themselves.…”
Section: Acceptabilitysupporting
confidence: 61%
“…Transcripts of the focus groups were analyzed following the template analysis approach as developed by King et al (2019), entailing a thematical analysis using a constructed coding template. The template was based on the research question and the theoretical concepts of organizational implementation management (Cosby, 2006;Eid & Quinn, 2017). Four broad code categories formed the code manual: knowledge, attitude, self-efficacy, and organizational infrastructure (see Appendix 1).…”
Section: Discussionmentioning
confidence: 99%